Double balloon catheter induction of labor in pregnant women with COVID-19 infection - Jiao Yi; Lei Chen; Xianglian Meng; Yi Chen (BMC Pregnancy and Childbirth)
Abstract Background To identify the effectiveness and safety induction using a double-balloon catheter in the setting of Coronavirus disease 2019 (COVID−19) infection. Methods This retrospective study included 577 COVID−19-afected women who underwent induction of labor with a double balloon catheter or spontaneously started delivery between December 7, 2022, and June 20, 2023; 154 women underwent induction of labor (double balloon catheter, study group) and 423 women underwent spontaneous started delivery (control group). Maternal and neonatal outcomes and complications during labor were assessed and compared. Results Duration of the first stage of labor and total labor in the study group were significantly shorter than those in the control group (P < 0.05). There were no statistically significant differences between the two groups in terms of maternal delivery complications (P > 0.05). The two groups did differ significantly in the occurrences of pregnancy induced hypertension and gestational diabetes mellitus (P < 0.05). The neonatal prognosis was similar between the two groups (P > 0.05). After adjusting for maternal age, body mass index, gestational age at delivery, gestational age at infection, gravidity, parity, oxytocin administration and failure of progress of labor, multivariate logistic regression analysis found that COVID−19-afected women who received the double balloon catheter were not associated with an increased risk of fetal distress, intrapartum fever and cesarean section (P > 0.05). Conclusions Double balloon catheter is an effective and safe method for labor induction in pregnant women with COVID−19 and is not associated with an increased risk of fetal distress, intrapartum fever and cesarean section.